2019
DOI: 10.1183/13993003.01530-2018
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary COPD intervention in primary care: a cluster randomised controlled trial

Abstract: We evaluated the effectiveness of an interdisciplinary, primary care-based model of care for chronic obstructive pulmonary disease (COPD).A cluster randomised controlled trial was conducted in 43 general practices in Australia. Adults with a history of smoking and/or COPD, aged ≥40 years with two or more clinic visits in the previous year were enrolled following spirometric confirmation of COPD. The model of care comprised smoking cessation support, home medicines review (HMR) and home-based pulmonary rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 41 publications
0
64
1
Order By: Relevance
“…Our findings resonate with ideas around needing more tailored interventions for people with frailty 76 and respiratory disease, 77 thinking creatively about engagement with exercise-based interventions, 78 and taking integrated approaches to support the maintenance of physical and mental capacities in an aging population. 79 Recent examples within wider respiratory care include interdisciplinary models of primary care for people with COPD, 80 integrated respiratory and palliative care services for chronic breathlessness, 81 and rehabilitation for people with both respiratory and heart disease. 82 As research specifically with people with COPD and frailty increases, 50,54 this type of complex interventional work will be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings resonate with ideas around needing more tailored interventions for people with frailty 76 and respiratory disease, 77 thinking creatively about engagement with exercise-based interventions, 78 and taking integrated approaches to support the maintenance of physical and mental capacities in an aging population. 79 Recent examples within wider respiratory care include interdisciplinary models of primary care for people with COPD, 80 integrated respiratory and palliative care services for chronic breathlessness, 81 and rehabilitation for people with both respiratory and heart disease. 82 As research specifically with people with COPD and frailty increases, 50,54 this type of complex interventional work will be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few trials directly demonstrated reduced hospitalization or rehospitalization; most have concentrated on other outcome measurements including quality of life and symptom improvement. 6,7,[17][18][19] The recent evidence of the integrated care management approach further supports the benefit of a multidisciplinary team to reduce ED visits and hospital admissions. 20 The streamlined unified meaningfully managed interdisciplinary team (SUMMIT) trial protocol shows further interest in the multidisciplinary approach to care in an urban homelessness setting; results of the trial are not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of a physical therapist, pharmacist, psychologist, dietitian, exercise specialists, and social workers varied by study and location. 7,17,22,23 There is no consensus agreement regarding the ideal makeup of a COPD team despite the multiple studies that have been conducted. Regardless of the disciplines involved, teams should establish interdependence among the members where the treatment plan and patient-specific goals combines the expertise of the individual disciplines involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the European Respiratory Journal, LIANG et al [5] present the results of a cluster randomised trial undertaken in primary care in Australia which investigated the effectiveness of an interdisciplinary bundle of interventions, comprising smoking cessation support, home medicines review by a pharmacist, and a home-based pulmonary rehabilitation programme (termed the "RADICALS model of care"). They used a case-finding approach to identify potential patients based on a smoking history on general practitioner (GP)'s records who, along with those with an existing coded diagnosis, were then eligible for the trial if baseline spirometry fulfilled diagnostic criteria for COPD.…”
mentioning
confidence: 99%